(untitled) (Research, Society and Development, 2020)
Never before in history has there been such a high volume of knowledge. Furthermore, the access to this information is simple and easy. However, for the individual to be able to store and express this knowledge, it is necessary to use methods of learning and storing the studied content. Considering the classification of Felder and Silverman (1988), it was carried out a research with a group of students from the inclusive technical courses in Buildings, and from the Bachelor of Civil Engineering. The idea was to know the perception of these students regarding the learning processes, as well as building and evaluating the profile of a classroom in which there are several individuals and, in general, they need to learn from a single way or teaching dynamic. This study aimed to identify the predominant learning style among students from the inclusive technical education and the college education in Civil Engineering from the Federal Institute of Minas Gerais (IFMG), Campus Piumhi, located in Brazil. The survey of learning styles was made by applying an online questionnaire from Google Forms, and the data was compiled through Microsoft Excel application. This research included 45 students from inclusive technical education and 94 students from college education in Civil Engineering. Through the data analysis, it was possible to verify that the majority of students from inclusive technical education have characteristics that classify them as sensory, visual, reflective, and global. Considering the Higher Education, most students classified themselves as sensory, visual, active, and sequential.